Hepatic Global DNA Hypomethylation Phenotype in Rainbow Trout Fed Diets Varying in Carbohydrate to Protein Ratio. Issue 1 (22nd September 2021) - Liu, Jingwei; Heraud, Cécile; Véron, Vincent; Laithier, Jésabel; Burel, Christine; Prézelin, Audrey; Panserat, Stéphane; Marandel, Lucie
ABSTRACT: Background: A high carbohydrate–low protein diet can induce hepatic global DNA hypomethylation in trout. The mechanisms remain unclear. Objectives: We aimed to investigate whether an increase in dietary carbohydrates (dHCs) or a decrease in dietary proteins (dLPs) can cause hepatic global DNA hypomethylation, as well as explore the underlying mechanisms in trout. Methods: Two feeding trials were conducted on juvenile males, both of which involved a 4-d fasting and 4-d refeeding protocol. In trial 1, trout were fed either a high protein–no carbohydrate [HP-NC, protein 60% dry matter (DM), carbohydrates 0% DM] or a moderate protein–high carbohydrate (MP-HC, protein 40% DM, carbohydrates 30% DM) diet. In trial 2, fish were fed either a moderate protein–no carbohydrate (MP-NC, protein 40% DM, carbohydrates 0% DM), an MP-HC (protein 40% DM, carbohydrates 30% DM), or a low protein–no carbohydrate (LP-NC, protein 20% DM, carbohydrates 0% DM) diet to separate the effects of dHCs and dLPs on the hepatic methylome. Global C m CGG methylation, DNA demethylation derivative concentrations, and mRNA expression of DNA (de)methylation-related genes were measured. Differences were tested by 1-factor ANOVA when data were normally distributed or by Kruskal–Wallis nonparametric test if not. Results: In both trials, global C m CGG methylation concentrations remained unaffected, but the hepatic 5-mdC content decreased after refeeding (1–3%). The MP-HC group had 3.4-fold higher hepatic 5-hmdC and a similar 5-mdC concentration compared with the HP-NC group in trial 1. Both MP-HC and LP-NC diets lowered the hepatic 5-mdC content (1–2%), but only the LP-NC group had a significantly lower 5-hmdC concentration ( P < 0.01) compared with MP-NC group in trial 2. Conclusions: dHC and dLP independently induced hepatic global DNA demethylation in trout. The alterations in other methylation derivative concentrations indicated the demethylation process was achieved through an active demethylation pathway and probably occurred at non-C m CGG sites.